The Profile of Students Activities; Before, During and After Learning - Fikriyanda Fikriyanda; Daharnis Daharnis; Verlanda Yuca (Universitas Negeri Padang, 2019)
Learning activities are a learning effort by students in physical, mental, intellectual, and emotional aspects from the to hard observed activities that happened inside or outside the classroom. This study describes students learning activities that will impact on student learning outcomes. The method used is descriptive-analysis with a 167 students sample that using proportional random sampling technique, used a questionnaire . The instrument used is a questionnaire. The result of the research is it includes the students learning activities in Junior High school in the medium category which comprises learning activities before learning in school, learning during school, and after learning in school. The implications of this research can be a reference and input for Counselor to improve students learning activities at 19 Junior High school in Bandung.